2016
DOI: 10.1530/erp-16-0008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and measuring fluid responsiveness with echocardiography

Abstract: Echocardiography is ideally suited to guide fluid resuscitation in critically ill patients. It can be used to assess fluid responsiveness by looking at the left ventricle, aortic outflow, inferior vena cava and right ventricle. Static measurements and dynamic variables based on heart–lung interactions all combine to predict and measure fluid responsiveness and assess response to intravenous fluid resuscitation. Thorough knowledge of these variables, the physiology behind them and the pitfalls in their use allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 32 publications
1
87
0
22
Order By: Relevance
“…In human medicine, evaluation of inferior vena cava diameter (IVC D ) and collapsibility index (IVC CI ) as well as the ratio of IVC compared with the aortic diameter (IVC/Ao) all have been evaluated to assess intravascular volume status. Studies suggest they correlate well with dynamic variables of intravascular volume assessment and can predict fluid responsiveness in intensive care unit patients . The IVC D predicts volume status in spontaneously breathing healthy volunteers, in patients with severe sepsis, acute circulatory failure, and heart failure, in patients undergoing hemodialysis, and even in patients receiving positive pressure mechanical ventilation …”
Section: Introductionmentioning
confidence: 90%
“…In human medicine, evaluation of inferior vena cava diameter (IVC D ) and collapsibility index (IVC CI ) as well as the ratio of IVC compared with the aortic diameter (IVC/Ao) all have been evaluated to assess intravascular volume status. Studies suggest they correlate well with dynamic variables of intravascular volume assessment and can predict fluid responsiveness in intensive care unit patients . The IVC D predicts volume status in spontaneously breathing healthy volunteers, in patients with severe sepsis, acute circulatory failure, and heart failure, in patients undergoing hemodialysis, and even in patients receiving positive pressure mechanical ventilation …”
Section: Introductionmentioning
confidence: 90%
“…Available reports suggested that LVOT‐VTI assessment could be considered enough to monitor short‐term changes in SV. Furthermore, LVOT‐VTI would be an appropriate and dynamic indicator of fluid responsiveness …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LVOT-VTI would be an appropriate and dynamic indicator of fluid responsiveness. 1,11 The measurements of LVOT and VTI-derived parameters have some advantages: (a) providing a CO surrogate that can be obtained easily and quickly with standard equipment widely available in health centers; (b) a good intra-and interobserver repeatability; 54…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations